Effect of Sodium to Calcium Activity Ratio and Residual Sodium Carbonate in Irrigation Water on Physico-chemical Properties of the Haplustalfs and Performance of Wheat (Triticum aestivum L.) - Singh, Laxman; Totawat, K L (Annals of Arid Zone, 2016)
Two texturally different, fine loamy (clay loam) and coarse loamy (sandy loam) mixed hyperthermic Haplustalfs were irrigated with waters of varying quality, prepared artificially using different levels of SCAR (Sodium to calcium activity ratio) and RSC (Residual sodium carbonate) to raise the wheat crop. The magnitude of change in physico-chemical properties is not identical at equivalent level of RSC in irrigation water. Increasing levels of SCAR from 7 to to and RSC from 0to 10me L-1Â in irrigation water decreased the electrical conductivity, hydraulic conductivity, water holding capacity and contents of organic carbon, soluble cations and anions and increased the pH and ESP of the soil. The effect on morphological characters, dry mailer yield and uptake of nutrient varied with Mg.Ca ratio in irrigation water and clay content of the soil. The reduction in plant growth, dry mailer yield and nutrient uptake was more pronounced at SCAR value of to in irrigation water and in soil finer in texture, indicating SCAR to be a beller index for judging the suitability of irrigation water than that of SAR.